A lighthearted approach to mindfulness: development and evaluation of a humor-enriched mindfulness-based program in a randomized trial - Kastner, Christian T. (Frontiers in Psychology, 2024)
Objectives: Recently, research on mindfulness and humor has begun to spark interest, both being essential contributors to well-being. This article proposes that forms of humor that share intention and attitudinal foundations with mindfulness, constitute the foundation of a mindful-humorous perspective and mindful humor. Once intention and attitude are in alignment, shared mechanisms underlying a mindful-humorous perspective may lead to synergetic effects (e.g., reinforcing a shift in perspective and attitudinal foundations) as summarized in the proposed mindful humor filter model. Based on this theoretical framework, the humor-enriched mindfulness-based program (HEMBP) was developed and its validity and efficacy were evaluated in a randomized controlled trial as a first step to test the newly introduced model. Methods: A total of 60 participants were randomly allocated to either the HEMBP or a wait-list control group. Participants' mindfulness, comic styles (e.g., benevolent humor, sarcasm, and cynicism), psychological well-being, life satisfaction, stress, and gelotophobia (fear of being laughed at) were assessed one week before and after training, and at a one-month follow-up. Linear mixed-effects models were fitted to model changes in outcome variables over time. Results: The HEMBP was effective in increasing mindfulness, benevolent humor, and psychological well-being, and in reducing sarcasm, cynicism, stress, and gelotophobia, compared to the control group. Conclusion: Results support the validity and efficacy of the HEMBP as a promising approach for improving well-being and reducing stress. The HEMBP broadens the scope of existing mindfulness-based programs by cultivating a mindful-humorous outlook on life, facilitating mindfulness practice and insights, and fostering positive emotions and relationships with others through mindful humor. Results are also suggestive of the validity of the mindful humor filter model.